Analyze the Educational Needs of Nurses in Kermanshah Ayatollah Taleghani Hospital in the Case of Preventing Occupational Risks Related to Biological Agents - Seyedeh Sara Hosseini (Journal of Global Pharma Technology, 2017)
Background: The most significant occupational injuries among nurses are associated with biological agents which include multiple underlying cases. Therefore, the design and implementation of educational programs with operational objectives and based on needs assessment on prevention of occupational risks can be increasingly effective on maintain and improvement of nursing staff health. Methods: Statistical population of this cross-sectional study includes Kermanshah Ayatollah Taleghani Hospital nurses and a sample of 70 nurses participated in study. Data collection tools included demographic information questionnaires and 10 items related to prevent nursing occupational hazards biological agents. When responses were evaluated, the collected data were analyzed using SPSS18 software, independent t, Spearman and Pearson tests and results were presented in terms of statistical indicators. Results: 30% of participants in study were nurse's aide and 70% were nurses. Two items are introduced as the first priority of educational needs including familiarity with transmissible diseases in wards or hospital and care oneself during disease, injury or skin lesions of hands until complete recovery. In most cases, there was statistically significant relationship between variables and items. Conclusion: Nurses' knowledge on safety rules is more important in prevention of occupational hazards and as a result, application of these principles. In this regard, considering biological agents has been focused and needs assessment of educational planning will be effective on increased participation of nurses in teaching and learning process and will promote their knowledge and skills.Keywords: Nurses, Nurse's aide, Occupational hazards, Biological agents.